Convergência entre televisão e narrativas imersivas : as potencialidades e os desafios das novas tecnologias de realidade virtual e dos vídeos 360 graus para transformar o futuro da televisão - Gauterio, Mariana Wichrowski (2019)
The Virtual Reality (RV) and the 360 degree videos have explored, through immersive narratives, a proposal of innovation for communication. The paper discusses how these immersive narratives are used in the field of social communication, exploring its main characteristics, as well as the possibilities of enjoyment in the television environment. We present the proposal of methodological procedures that include the literature review with the study of the theoretical currents, from the concepts of technological imaginary, immersive narratives, new technologies, convergence and transmedia, digital television and virtual reality. This doctoral dissertation exposes the results of an exploratory / qualitative research, through the analysis of the convergence between what is understood by traditional media and new media. For this, in a complex phenomenon, the sociology of understanding, based on Maffesoli (2010), was elected. As methodology, the case study was based on multiple case studies (YIN, 2015). Based on the observations made, this doctoral dissertation proposes to study the mysteries between the attempt of convergence between television and the immersive narratives based on technologies of virtual reality and in the videos in 360 degrees, focusing on the relation between them and how this product is being presented to the final public, in order to provide immersive experiences in a television environment. We conclude that there is a latent attempt in the market to appropriate the immersive narratives through virtual reality technologies and 360º videos in the television environment. However, these immersive narratives, based on 3D environments, adapted for screens designed to receive 2D content, as is the case of television, do not become initiatives of great immersive expression for the final public.